VALIDATION OF THE SHORT FORM OF THE INTERNATIONAL CROWDING MEASURE IN EMERGENCY DEPARTMENTS (ICMED): INTERNATIONAL STUDY. Issue 12 (18th November 2016) - Boyle, A; Richter, S; Atkinson, P; Clouston, R; Stoica, G; Basaure Verdejo, C; Wakai, A; Chan, E; Grewal, K; Gilligan, P; Higginson, I; Liston, P; et al.
Abstract : Objectives & Background: There is little consensus on the best way to measure emergency department crowding. We have previously developed a consensus based measure, the International Crowding Measure in Emergency Departments (ICMED). This measure has both flow and non-flow items, and also contains items which measure Input, Throughput and Output. We aimed to externally validate a short form of the ICMED against emergency physician's perceptions of crowding and danger across a wide variety of Emergency Departments. Face validity is important to support implementation of any measure Methods: We performed an observational validation study in seven emergency departments in five different countries. We recorded sICMED observations and the most senior available emergency physician's perceptions of crowding and danger at the same time. We performed a times series regression model to account for clustering and correlation. Results: 397 data points were analysed. The sICMED showed moderate positive correlations with emergency physician's perceptions of crowding r=0.4110, p<0.05) and danger (r=0.4566, p<0.05.) There was considerable variation in the performance of the sICMED between different emergency departments. The sICMED was only slightly better than measuring occupancy or emergency department boarding time. Conclusion: The short form of the ICMED has moderate face validity in measuring crowding. This is an important first step in validating this measure. The measure performs less well in Emergency Departments that are constantly crowded.Figure 1